Effect of Homologous and Heterologous Booster in COVID-19 Vaccination - Marija Vukčević; Mateja Despot; Aleksandra Nikolić-Kokić; Duško Blagojević; Milan Nikolić; Ana Banko; Tanja Jovanović; Dragana Despot (Pharmaceuticals)
Background: COVID-19 became a global health crisis in early 2020, and the way out of the crisis was the rapid development of vaccines by Sinopharm, Pfizer, and Sputnik, among others, which played a crucial role in controlling the pandemic. Therefore, this study aims to investigate the long-term immune response by measuring the levels of anti-S1 IgG antibodies induced by homologous and heterologous vaccination regimens. Methods: We investigated the titer of the anti-S1 IgG antibody produced for the viral surface antigen 3, 6 months after the second dose, before the third dose, and 1, 3, and 6 months after the third dose. Results: Anti-S1 IgG antibody levels significantly increased three/six months after the second dose and following the booster in individuals without prior COVID-19 infection who received all three homologous vaccine doses. The group that initially responded poorly to Sinopharm showed a significant and sustained increase after receiving the Pfizer booster. Additionally, prior SARS-CoV-2 infection between primary and booster vaccination boosted anti-S1 antibody titers in all individuals, regardless of the vaccine used. The highest vaccine efficacy was observed during the primary vaccination period and declined over time, especially during the omicron-dominant period. Conclusions: The results suggest that while homologous and heterologous booster doses can significantly enhance anti-S1 IgG antibody levels, prior SARS-CoV-2 infection and the type of vaccine administered influence the duration and magnitude of the immune response.